Gene set enrichment analysis of the bronchial epithelium implicates contribution of cell cycle and tissue repair processes in equine asthma. Issue 1 (December 2018) - Tessier, Laurence; Côté, Olivier; Clark, Mary; Viel, Laurent; Diaz-Méndez, Andrés; Anders, Simon; Bienzle, Dorothee
Abstract Severe equine asthma is a chronic inflammatory condition of the lower airways similar to adult-onset asthma in humans. Exacerbations are characterized by bronchial and bronchiolar neutrophilic inflammation, mucus hypersecretion and airway constriction. In this study we analyzed the gene expression response of the bronchial epithelium within groups of asthmatic and non-asthmatic animals following exposure to a dusty hay challenge. After challenge we identified 2341 and 120 differentially expressed genes in asthmatic and non-asthmatic horses, respectively. Gene set enrichment analysis of changes in gene expression after challenge identified 587 and 171 significantly enriched gene sets in asthmatic and non-asthmatic horses, respectively. Gene sets in asthmatic animals pertained, but were not limited, to cell cycle, neutrophil migration and chemotaxis, wound healing, hemostasis, coagulation, regulation of body fluid levels, and the hedgehog pathway. Furthermore, transcription factor target enrichment analysis in the asthmatic group showed that transcription factor motifs with the highest enrichment scores for up-regulated genes belonged to the E2F transcription factor family. It is postulated that engagement of hedgehog and E2F pathways in asthmatic horses promotes dysregulated cell proliferation and abnormal epithelial repair. These fundamental lesions may prevent re-establishment of homeostasis and perpetuate inflammation.